Women of sand and myrrh - Shaykh, Ḥanān (Anchor Books, 1992)
Little is known of what life is like for contemporary Arab women living in the Middle East. One of the few literary voices speaking out from that still closed society is Hanan al-Shaykh, whose novel The Story of Zahra was banned in most Arab countries. Now available for the first time in the U.S. is her newest novel, a story of four women treated to every luxury but freedom.